The impact of urban models on social support – Between spatial justice and sustainable development - Lorena Fiorini; Lucia Saganeiti; Matteo Perazzini; Danilo Bontempo; Martina Bucci; Marco Giancola; Enrico Perilli (Agathón)
Territorial disparities condition the well-being of communities, affecting access to essential services and the possibility of building and maintaining meaningful social networks. Differences in the distribution of infrastructure, the quality of urban spaces, and opportunities for social interaction can amplify isolation situations, especially impacting the most vulnerable segments of the population. This study, conducted in four municipalities in the Province of L’Aquila, analyses the phenomenon according to two dimensions: the spatial one, linked to urban planning and the location of primary services, and the social one, related to perceived social support. The results underline the importance of inclusive planning that promotes spatial justice and equitable access to services, in line with the Sustainable Development Goals.